Innovation of 3D-printed waste-derived graphene oxide for water treatment via digital light processing - Mohd Nizam, Nur Hazirah; Badrol Hisam, Zata Azhani; Zazani, Ahmad Hafizuddin (2024)
Water scarcity and contamination are pressing concerns that global society must address. Water supply and distribution infrastructure have barely improved despite urbanisation and community development. Broken pipes and heavy metal contamination from old, corroded pipelines may produce silt buildup, harbouring microbiological contaminants due to low chlorine levels. The technological limitations of conventional filtering technologies, which do not meet modern water treatment needs, may not efficiently eliminate all forms of waterborne pathogens. Therefore, this study focuses on advancing antibacterial filtration membranes for water filtration. This study presents artificial design structures integrating waste-derived graphene oxide (GO) into a membrane matrix via the additive manufacturing (AM) technique. This study aims to fill the membrane technology innovation gap by exploring new membrane fabrication alternatives involving designing and fabricating membranes using Digital Light Processing (DLP) to quickly print two-dimensional structural layers. Membrane performance will be optimised through spectroscopy, antibacterial analysis, water permeability, and selectivity analysis. This filtration membrane is unique in the realm of novel material composition. Interestingly, GO's hydrophilic oxygen functional group yields a strong affinity for water to other contaminants, allowing water to flow over its surface without experiencing friction. This facilitates the production of membranes with improved permeability, simultaneously addressing two critical aspects of water contamination by increasing the specific surface area and lowering membrane fouling. Considering the expansion of the global 3D printing market, the discoveries from this study could pave the way for a new manufacturing approach for producing filtration membranes utilising a diverse range of materials. This study aligns with the broader strategy to meet the Sustainable Development Goals (SDG), specifically SDG6, SDG9 and SDG11 and is situated within the framework of the Fourth Industrial Revolution (IR 4.0) with a particular focus on additive manufacturing of membrane designs for water.